Categorizing community type for epidemiologic evaluation of community factors and chronic disease across the United States. Issue 1 (2022) - McAlexander, Tara P.; Algur, Yasemin; Schwartz, Brian S.; Rummo, Pasquale E.; Lee, David C.; Siegel, Karen R.; Ryan, Victoria; Lee, Nora L.; Malla, Gargya; McClure, Leslie A.
Abstract: Existing classifications of community type do not differentiate urban cores from surrounding non-rural areas, an important distinction for analyses of community features and their impact on health. Inappropriately classified community types can introduce serious methodologic flaws in epidemiologic studies and invalid inferences from findings. To address this, we evaluate a modification of the United States Department of Agriculture's Rural Urban Commuting Area codes at the census tract, propose a four-level categorization of community type, and compare this with existing classifications for epidemiologic analyses. Compared to existing classifications, our method resulted in clearer geographic delineations of community types within urban areas. Highlights: Epidemiology studies of place-based factors that encompass a variety of community types are prone to methodological challenges. Stratification by appropriate definitions of community type can mitigate these challenges. We demonstrate a method for categorizing community type at the census tract level in the United States. Compared to previously published methods, our new modification better differentiates urban cores from surrounding suburban and non-rural areas.